How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

Strategic Network Disruption and Defense - Hoyer, Britta; De Jaegher, Kris (Journal of Public Economic Theory)
We study a game between a network designer, who uses costly links to connect nodes in a network, and a network disruptor who tries to disrupt the resulting network as much as possible by deleting either nodes or links. For low linking costs networks with all nodes in symmetric positions are a best response of the designer under both link deletion and node deletion. For high linking costs the designer builds a star network under link deletion, but for node deletion excludes some nodes from the network to build a smaller but stronger network. For intermediate linking costs the designer again builds a symmetric network under node deletion but a star‐like network with weak spots under link deletion.

Herausforderungen im Umgang mit unvollständigen Softwareanforderungen durch Semantic Role Labeling - Reckhorn, Lena

‚Reden‘ über Dichtung. Poetik-Vorlesungen und Poetik-Dozenturen im literarischen Feld - Eke, Norbert Otto (Text + Kritik X/16, Sonderband: Poetik des Gegenwartsromans. Hg. von Nadine J. Schmidt und Kalina Kupczyńska)

„Um so etwas bekümmre ich mich nicht“. Grabbe und die Moral - Eke, Norbert Otto (Text + Kritik IX/16)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, Dirk Florian; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)

By-product mutualism and the ambiguous effects of harsher environments – A game-theoretic model - De Jaegher, Kris; Hoyer, Britta (Journal of Theoretical Biology)
We construct two-player two-strategy game-theoretic models of by-product mutualism, where our focus lies on the way in which the probability of cooperation among players is affected by the degree of adversity facing the players. In our first model, cooperation consists of the production of a public good, and adversity is linked to the degree of complementarity of the players׳ efforts in producing the public good. In our second model, cooperation consists of the defense of a public, and/or a private good with by-product benefits, and adversity is measured by the number of random attacks (e.g., by a predator) facing the players. In both of these models, our analysis confirms the existence of the so-called boomerang effect, which states that in a harsh environment, the individual player has few incentives to unilaterally defect in a situation of joint cooperation. Focusing on such an effect in isolation leads to the "common-enemy" hypothesis that a larger degree of adversity increases the probability of cooperation. Yet, we also find that a sucker effect may simultaneously exist, which says that in a harsh environment, the individual player has few incentives to unilaterally cooperate in a situation of joint defection. Looked at in isolation, the sucker effect leads to the competing hypothesis that a larger degree of adversity decreases the probability of cooperation. Our analysis predicts circumstances in which the "common enemy" hypothesis prevails, and circumstances in which the competing hypothesis prevails.

Der Reisende Müller - Eke, Norbert Otto (Reiseliteratur der DDR. Bestandsaufnahme und Modellanalysen)

Grabbes und Büchners Zeithorizonte - Eke, Norbert Otto (Innovation des Dramas im Vormärz: Grabbe und Büchner)

Das Politische und die Politik im Vormärz - Eke, Norbert Otto; Füllner, Bernd (Das Politische und die Politik im Vormärz)

„Aus wenigen Phonemen erstehen Welten in der Vorstellung des Zuschauers.“ Werner Fritsch: Autor, Regisseur – Visionär - Eke, Norbert Otto (Werner Fritsch: Nofretete / Das Rad des Glücks / Mutter Sprache)

„Zeit ist geblieben / Zeit ohne Zeit“. Chronotopische Konstruktionen im Werk Herta Müllers - Eke, Norbert Otto (Herta Müller und das Glitzern im Satz. Eine Annäherung an Gegenwartsliteratur)

„Wir kommen/Ins Heilige hinein/Noch auch“. Zum Religiösen als Paradigma der deutschsprachigen Gegenwartsliteratur - Eke, Norbert Otto (Kultur und Religion. Eine interdisziplinäre Bestandsaufnahme)

Das Junge Deutschland und der Europagedanke - Eke, Norbert Otto (Europa im Vormärz. Eine transnationale Spurensuche)

„Nischt! Immermannscher Wust!“ Karl Immermann und das Theater im Vormärz - Eke, Norbert Otto (Immermanns theatralische Sendung. Karl Leberecht Immermanns Jahre als Dramatiker und Theaterintendant in Düsseldorf (1827-1837))

Drei im gestimmten Raum. Lea Singers Verdis letzte Versuchung - Eke, Norbert Otto („Ei, dem alten Herrn zoll ich Achtung gern“. Festschrift für Joachim Veit zum 60. Geburtstag)
Angaben zur Herausgeberschaft: Hg. von Kristina Richts und Peter Stadler für den virtuellen Forschungsverbund Edirom

Goals as Reference Points: Empirical Evidence from a Virtual Reward System - von Rechenberg, Tobias; Gutt, Dominik; Kundisch, Dennis (Decision Analysis)
Heath et al. (1999) propose a prospect theory model for goal behavior. Their analytical model is based on the assumption that goals inherit the main properties of the prospect theory value function, i.e., reference point dependence, loss aversion, and diminishing sensitivity. We investigate whether these main properties transfer to goal behavior in the field. We take user activity data from a gamified Question & Answer community and analyze how users adjust their contribution behavior in the days surrounding goal achievement, where goals are represented by badges. We find that users gradually increase their performance in the days prior to earning a badge, with performance peaking on the day of the promotion. In subsequent days, user performance gradually diminishes again, with the decline being strongest on the day immediately following the badge achievement. These findings reflect the characteristic S-shape of the prospect theory value function which is convex below the reference point and concave above it. Employing the target-based approach, we can interpret the value function as a cumulative density function of a unimodal probability distribution. Our results suggest that it is more likely that active members of the community focus on the next badge relative to the status already achieved, as their next goal and are less likely to focus on more remote (higher-ranked) badges. Our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals.

Gefälschte Online Bewertungen - Literaturüberblick - Sassenberg, Tristan

Valentin, Thomas - Eke, Norbert Otto (Neue Deutsche Biographie Bd. 26)

Supporting Additive Manufacturing by Augmented Reality - Gräßler, Iris; Taplick, Patrick (6th International Conference on Additive Technologies iCAT 2016)

Szenario-basierte Analyse von Anforderungen im Produktentwicklungsprozess - Gräßler, Iris; Scholle, Philipp (Design for X, 27. Dfx-Symposium)

Eleven Potentials for mechatronic V-model - Gräßler, Iris; Hentze, Julian; Yang, Xiaojun (Production Engineering and Management, 6th International Conference, Band 01/2016)

Identification of indirect influences under time-variant impacts in scenario technique for foresight - Gräßler, Iris; Scholle, Philipp (R&D Management Conference 2016)

Enhancing Systems Engineering by Scenario-based Anticipation of Future Developments - Gräßler, Iris; Hentze, Julian; Scholle, Philipp (SoSe2016, 11th International Conference on System of Systems Engineering Conference)

Educational Learning Factory of a holistic Product Creation Process; 6th CLF - 6th CIRP Conference on Learning Factories

Interdisciplinary development of production systems using Systems Engineering - Gräßler, Iris; Yang, Xiaojun (26th CIRP Design Conference)

Enhancing scenario technique by time-variant impacts - Gräßler, Iris; Scholle, Philipp (DS 84, Proceedings of the DESIGN 2016 14th International Design Conference, Band 2)

VDI-Statusbericht: Digitale Chancen und Bedrohungen - Geschäftsmodelle für Industrie 4.0

Kapitel: Additive Fertigungsverfahren im Kontext von Industrie 4.0 - Klemp, Eric; Pottebaum, Jens (Handbuch Industrie 4.0: Produktion, Automatisierung und Logistik)

Assessing the accuracy of improved force-matched water models derived fromAb initiomolecular dynamics simulations - Köster, Andreas; Spura, Thomas; Rutkai, Gábor; Kessler, Jan; Wiebeler, Hendrik; Vrabec, Jadran; Kühne, Thomas D. (Journal of Computational Chemistry)

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

A Theoretical Analysis of the Fuzzy K-Means Problem - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin (2016 IEEE 16th International Conference on Data Mining (ICDM))
One of the most popular fuzzy clustering techniques is the fuzzy K-means algorithm (also known as fuzzy-c-means or FCM algorithm). In contrast to the K-means and K-median problem, the underlying fuzzy K-means problem has not been studied from a theoretical point of view. In particular, there are no algorithms with approximation guarantees similar to the famous K-means++ algorithm known for the fuzzy K-means problem. This work initiates the study of the fuzzy K-means problem from an algorithmic and complexity theoretic perspective. We show that optimal solutions for the fuzzy K-means problem cannot, in general, be expressed by radicals over the input points. Surprisingly, this already holds for simple inputs in one-dimensional space. Hence, one cannot expect to compute optimal solutions exactly. We give the first (1+eps)-approximation algorithms for the fuzzy K-means problem. First, we present a deterministic approximation algorithm whose runtime is polynomial in N and linear in the dimension D of the input set, given that K is constant, i.e. a polynomial time approximation scheme (PTAS) for fixed K. We achieve this result by showing that for each soft clustering there exists a hard clustering with similar properties. Second, by using techniques known from coreset constructions for the K-means problem, we develop a deterministic approximation algorithm that runs in time almost linear in N but exponential in the dimension D. We complement these results with a randomized algorithm which imposes some natural restrictions on the sought solution and whose runtime is comparable to some of the most efficient approximation algorithms for K-means, i.e. linear in the number of points and the dimension, but exponential in the number of clusters.
Keywords: unsolvability by radicals; clustering; fuzzy k-means; probabilistic method; approximation algorithms; randomized algorithms

Machbarkeitsstudie 3D Druck Elektromotoren - Lammers, Stefan; Quattrone, Francesco; Mrozek, Rafael

Effects of innovative science and mathematics teaching on student attitudes and achievement: A meta-analytic study - Savelsbergh, Elwin R.; Prins, Gjalt T.; Rietbergen, Charlotte; Fechner, Sabine; Vaessen, Bram E.; Draijer, Jael M.; Bakker, Arthur (Educational Research Review)

Science Kits: Learning chemistry in a context-oriented learning environment - Fechner, Sabine; Sumfleth, Elke (Teachers creating context-based learning environments in science)

Egg-races als gesellschaftsfähige naturwissenschaftliche Wettbewerbe für jedermann? - Fechner, Sabine; Dettweiler, Yvonne; Sieve, Bernhard; Ulrich, Nina; Böhm, Dominic; Schanze, Sascha (CHEMKON)

Trendbericht Chemiedidaktik: Von Exklusion zur Inklusion - Becker, Hans-Jürgen; Fechner, Sabine; Brauckschulze, Lisa (Nachrichten aus der Chemie)

A comparative study of different amine-based solvents for CO2-capture using the rate-based approach - Hüser, Nicole; Schmitz, Oliver; Kenig, Eugeny (Chemical Engineering Science)

Vergleich von MEA und AMP als Lösungsmittel für die CO2-Abscheidung mit Hilfe des rate-based Ansatzes - Hüser, Nicole; Schmitz, Oliver; Kenig, Eugeny

Eine neue Rippengeometrie zur Verbesserung des Wärmeübergangs in flüssigkeitsdurchströmten Kanälen - Zibart, Alexander; Cherkezova, Rositsa; Figge, Heiko; Kenig, Eugeny

Economic Aspects of Service Composition: Price Negotiations and Quality Investments - Brangewitz, Sonja; Hoof, Simon (Service-Oriented and Cloud Computing: 5th IFIP WG 2.14 European Conference, ESOCC 2016, Vienna, Austria, September 5-7, 2016, Proceedings)
We analyse the economic interaction on the market for composed services. Typically, as providers of composed services, intermediaries interact on the sales side with users and on the procurement side with providers of single services. Thus, in how far a user request can be met often crucially depends on the prices and qualities of the different single services used in the composition. We study an intermediary who purchases two complementary single services and combines them. The prices paid to the service providers are determined by simultaneous multilateral Nash bargaining between the intermediary and the respective service provider. By using a function with constant elasticity of substitution (CES) to determine the quality of the composed service, we allow for complementary as well as substitutable degrees of the providers' service qualities. We investigate quality investments of service providers and the corresponding evolution of the single service quality within a differential game framework.

Entwicklung von Bewertungsmethoden und Richtlinien für das Kleben von ZnMgAl-legierungsbeschichteten Stahlfeinblechen - Ditz, Michael; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido

Entwicklung von Bewertungsmethoden und -richtlinien für das Kleben von ZnMgAl-beschichteten Stahlfeinblechen - Ditz, Michael; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido (6.Doktorandenseminar Klebtechnik)

Object oriented graphical user interface development methodologies for distribution smart grid applications - Hrnjić, Tarik; Huseinagić, Indira; Pašić, Faruk (2016 XI International Symposium on Telecommunications (BIHTEL))

Analyse der Schwingfestigkeit geklebter Stahlverbindungen unter mehrkanaliger Belastung - Nagel, C.; Fiedler, A.; Brede, M.; Çavdar, Serkan; Meschut, Gerson; Kroll, U.; Matzenmiller, A.; Rybar, G.; Melz, T. (16. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Die Wirkung von monetären Incentives auf das Bewertungsverhalten von Kunden am Beispiel von meineLinse.de - Funke, Julia

A Comparison of Frontal Theta Activity During Shooting among Biathletes and Cross-Country Skiers before and after Vigorous Exercise. - Luchsinger, H; Ø, Sandbakk; Schubert, M; Ettema, G; Baumeister, Jochen (PLoS One)

The Europeanization of Commercial Agency Law - Krimphove, Dieter (La Europeización del Derecho Privado: Cuestiones Actuales)

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Structure and Online Rating Distributions - Herrmann, Philipp; Gutt, Dominik; Rahman, Mohammad (INFORMS Annual Meeting)